Design and Build Innovative Maximum Simple Manual Briquette Printer (Brimax) - Dwi Hari Winarno; Dyah Ayu Sri Hartanti; Siti Aminatuz Zuhria (AGARICUS: Advances Agriculture Science & Farming, 2023)
This study aims to find out how to work (manual briquette printer with maximum results) the results of designs that use manual power and to find out how the effect of the number of presses on changes in print volume. The research method used is an experimental method by conducting direct experiments in the field. This study used a Complete Randomized Design (RAL) with a variety of treatments consisting of P1 (3 times the number of presses), P2 (2 times the number of presses), and P3 (1 times the number of presses). Each treatment was repeated nine times, resulting in a total of 27 experimental units. The parameter observed is the effect of the number of presses on the change in the volume of the printout. The research data were analyzed using diversity analysis (Anova Table) at the level of 5%. The results showed that the treatment had a significant effect on the pressure count parameter on the change in print height. The best results were obtained in treatment 1 and 2, namely 3 and 2 times the number of presses with an average height of 1.8 cm, while the lowest results were obtained in treatment 3, which was 1 time the number of presses with an average height of 2.1 cm, because it was lower briquettes, the better the quality. The advantage of Brimax is that it is efficient in labor and cost and allows setting the quality of printouts